An Analysis of the Assembly Line Modernization by Using Simulation Software - Sujova, Erika; Strihavkova, Elena; Cierna, Helena (Manufacturing Technology Journal, 2018)
The article deals with the optimization and modernization of assembly systems by creating models in the simulation software. The creation of digital models is a current trend in enterprise digitization called Industry 4.0. The Tecnomatix Plant Simulation environment allows you to create a virtual model of a real assembly line with the input of its basic production parameters. To perform the analysis, 8 real assembly lines were used, with an average of 15 workplaces, which were integrated into one universal line by means of simulation. The aim was to analyse the effectiveness of the proposed modernization universal assembly line using the generated statistical data.
Keywords: simulation; virtual model; Industry 4.0; Tecnomatix Plant Simulation (TPS); assembly line; quality of processes